Dietary Habits and Nutrient Intakes Are Associated to Age-Related Central Auditory Processing Disorder in a Cohort From Southern Italy - Lampignano, Luisa; Quaranta, Nicola; Bortone, Ilaria; Tirelli, Sarah; Zupo, Roberta; Castellana, Fabio; Donghia, Rossella; Guerra, Vito; Griseta, Chiara; Pesole, Pasqua Letizia; Chieppa, Marcello; Logroscino, Giancarlo; et al. (Frontiers in Aging Neuroscience, 2021)
Objectives Central auditory processing disorder (CAPD) commonly occurs in older age. However, few studies of a possible link between age-related CAPD and diet in an older population have been conducted. The objective of the present study was to investigate the relationship between eating habits and age-related CAPD in a population >65 years, using cross-sectional and retrospective data obtained in the same population-based study about 12 years ago. Methods We selected 734 participants (403 men) from a large population-based study. For age-related CAPD assessment, we used the Synthetic Sentence Identification with Ipsilateral Competitive Message test. Dietary habits were assessed by a Food Frequency Questionnaire. Associations between age-related CAPD and food groups/macro-and micronutrients were explored using adjusted logistic regression models. Results Age-related CAPD subjects consumed more dairy (111 vs. 98 g/d), olives and vegetable oil (63 vs. 52 g/d) and spirits (2 vs.1 g/d), and less fruits (536 vs. 651 g/d) in the cross-sectional analysis. Age-related CAPD subjects had a lower intake of potassium, vitamin C, and a higher fat intake. Further analyses identified dietary fiber as being inversely related to age-related CAPD. Discussion The present study provided evidence that the dietary hypotheses proposed for explaining the development of cognitive disorders in older age might also hold for age-related CAPD. Further data from other large and prospective population-based studies are needed for confirming these findings.